CHANGES OF BIOCHEMICAL MARKERS OF BONE METABOLISM IN HIP JOINT OSTEOTOMY - TAKAGI, Yasushi; HIRAIZUMI, Yutaka; MIKUMO, Hitoshi; HOSINO, Yushi (Journal of The Showa Medical Association, 2000)
The purpose of this study was to define the changes in serum calcium (Ca), inorganic phosphorus (P), total and bone-type alkaline phosphatase (ALP), osteocalcin (OC) and calcitonin (CT) after osteotomy, and to know the bone metabolic properties during the early period of bone healing. The subjects were 11 cases (1 male and 10 female, 16-61 years, mean age: 39.6 years) who underwent osteotomy of the hip joint. Samples of venous blood were taken before and on days 3, 7, 14, 21 and 28 after the operation. Ca, P and total ALP activity were measured by the recommended methods, and bone-type ALP (B-ALP) activity was measured by electrophoresis. OC was measured by radioimmunoassay and CT was measured by a newly developed chemiluminescent immunoassay. Ca concentration decreased, reaching the lowest value by day 3 and returned to the pre-operative value by day 14. P concentration decreased, reaching the lowest value by day 3 and increased significantly by day 21. B-ALP activity fell by day 7 and started to increase to day 21. OC concentration significantly decreased by day 3 and then increased throughout the period. In contrast, CT concentration rose during the first 3 days and decreased week by week. According to the rise of B-ALP, osteoblast activity can be accelerated on about day 7 after osteotomy. The changes of OC and CT reflected the bone resorption and formation at the fracture site. Further investigations are required to determine the clinical significance of biochemical markers to estimate the prognosis of healing after bone fracture.